Governança corporativa para sucessão em empresas familiares: um estudo de caso do Grupo Votorantim - Alves, Silvio Lucas de Oliveira (2023)
The topic covered in this work refers to “Corporate Governance for succession in family businesses”. Therefore, Corporate Governance comprises a topic of utmost importance for all companies, and especially in the case of family businesses. This work aimed to understand and analyze how family businesses can adopt corporate governance efficiently, so that they can have longevity and good succession. The methodology included a literary review and a case study that analyzed a large family company: the Votorantim Group. The results showed that throughout its 90-year history, the company faced competition between industries, based on the existence of a competitive market that was undergoing intense globalization movements. Thus, to overcome the demands, since the beginning of its history, the Votorantim Group began to organize and plan for the development of a governance and management model that met the new demands of the market, placing emphasis on the long term, from the continuation of its ethical, moral and cultural values. The group has an education program in which heirs are included from an early age, so that the process of training and preparation for the succession process occurs in appropriate and expected conditions. It is concluded that the Votorantim Group represents a promising example to be followed when it comes to family business succession